The physics and applications of high brightness electron beams : (World Scientific, 2003)
This book contains the contributions to the Workshop on the Physics and Applications of High Brightness Electron Beams, held in July 2002 in Sardinia, Italy. This workshop had a broad international representation from the fields of intense electron sources, free-electron lasers, advanced accelerators, and ultra-fast laser-plasma, beam-plasma and laser-beam physics. The interdisciplinary participants were brought together to discuss advances in the creation and understanding of ultra-fast, ultra-high brightness electron beams, and the unique experimental opportunities in frontier high-energy-density and radiation-source physics which are offered by these scientific tools.